-7a-2b+3a-6b=

Simple and best practice solution for -7a-2b+3a-6b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7a-2b+3a-6b= equation:


Simplifying
-7a + -2b + 3a + -6b = 0

Reorder the terms:
-7a + 3a + -2b + -6b = 0

Combine like terms: -7a + 3a = -4a
-4a + -2b + -6b = 0

Combine like terms: -2b + -6b = -8b
-4a + -8b = 0

Solving
-4a + -8b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '8b' to each side of the equation.
-4a + -8b + 8b = 0 + 8b

Combine like terms: -8b + 8b = 0
-4a + 0 = 0 + 8b
-4a = 0 + 8b
Remove the zero:
-4a = 8b

Divide each side by '-4'.
a = -2b

Simplifying
a = -2b

See similar equations:

| 3y^2+y=1 | | 38=5(2x-3)+3x+1 | | -6(8+6p)+6p=-6p | | x+662=3y | | .40x+.20(40)=.20(74) | | -7c(5x-7)6(6x)+28(5x-7)10(6x)-14c(5x-7)4(24)= | | 16-5p+p=10 | | 5x=2x+22+x | | 3(3+x)=2x+4 | | -40+n=8(8n-5) | | 2.5(x-3)-3+1.7x=10.8(x+1.5) | | (6y^1/2)/(x^4/3)=(12y/x^1/3) | | 5x+8-x=6(x-1) | | -1/9(-3/4)= | | 5m-3/2=6 | | (x^3)+(3x^2)+(-9x)-(12)=0 | | (x^3)+(3x^2)+(-4x)-(12)=0 | | y=-cos(5x) | | (x^3)+(3x^2)+(4x)-(12)=0 | | 9q-(q-4)=4q+(q+1) | | 7m^2=-6-17m | | (x^3)+(3x^2)+(-6x)-(12)=0 | | m-14=n | | (x^3)+(3x^2)+(6x)-(12)=0 | | (x^3)+(3x^2)+(Kx)-(12)=0 | | 3(z+6)=2(z-3)+z | | 6x-36=10x+5 | | -14=-4(8x-8)-7(6x-4) | | -4-40k=-4.5-39k | | -9.5a-6+12a=-2 | | x-1/2×1/2=1/8 | | C(10,2)=10!/(10-2)!) |

Equations solver categories